Changes in Children's Language in the Pre-Post Puberty Period in the Karangasem Area - Ni Made Novi Dwi Cahyani; Ni Nyoman Padmadewi (Jurnal Penelitian Mahasiswa Indonesia, 2022)
This research is motivated by two problems, firstly language as a communication instrument used by children, and secondly children as users and users of language. In terms of language, we can observe that the nature of language is very dynamic and tends to change. Meanwhile, in terms of language users, we can also observe the dynamics of language that occurs in children continuously. The aims of this study were to: 1) Determine the language changes of children who are transitioning from pre-pubertal to early post-pubertal 2) To determine the language changes in the post-pubertal period in the relationship between language and thought; whether language affects the mind, or thoughts that affect language change. 3) Knowing the relationship between language changes and language politeness in the pre-post-pubertal period.This research is a qualitative descriptive research. This research was conducted through observation of empirical facts and phenomena witnessed by researchers as they are. Therefore, all visible phenomena are recorded and detailed without considering right or wrong. Thus this study seeks to provide a reflection of the data obtained from the object of research directly.The findings of this study are 1) Pre-pubertal language changes undergo a transition due to age and relationships built by speakers in the post-pubertal period. 2) The language of children who are experiencing a transition period is reciprocal with their thoughts. Therefore, language at the post-pubertal period can affect thoughts and thoughts can also affect a person's language changes. 3) The politeness of a child's language in the post-pubertal period cannot be seen through politeness norms alone but must also look at the language solidarity factor of peers for speakers and speakers in the principle of speech cooperation.